Behavioral Analysis of Genetically Modified Mice Indicates Essential Roles of Neurosteroidal Estrogen - Harada, Nobuhiro; Wakatsuki, Toru; Honda, Shin-ichiro (Frontiers in Endocrinology, 2011)
Aromatase in the mouse brain is expressed only in the nerve cells of specific brain regions with a transient peak during the neonatal period when sexual behaviors become organized. The aromatase-knockout (ArKO) mouse, generated to shed light on the physiological functions of estrogen in the brain, exhibited various abnormal behaviors, concomitant with undetectable estrogen and increased androgen in the blood. To further elucidate the effects of neurosteroidal estrogens on behavioral phenotypes, we first prepared an brain-specific aromatase transgenic (bsArTG) mouse by introduction of a human aromatase transgene controlled under a −6.5 kb upstream region of the brain-specific promoter of the mouse aromatase gene into fertilized mouse eggs, because the −6.5 kb promoter region was previously shown to contain the minimal essential element responsible for brain-specific spatiotemporal expression. Then, an ArKO mouse expressing the human aromatase only in the brain was generated by crossing the bsArTG mouse with the ArKO mouse. The resulting mice (ArKO/bsArTG mice) nearly recovered from abnormal sexual, aggressive, and locomotive (exploratory) behaviors, in spite of having almost the same serum levels of estrogen and androgen as the adult ArKO mouse. These results suggest that estrogens locally synthesized in the specific neurons of the perinatal mouse brain directly act on the neurons and play crucial roles in the organization of neuronal networks participating in the control of sexual, aggressive, and locomotive (exploratory) behaviors.